Photoacoustic spectroscopy as a method in biological investigations - MOTYLEWSKI, Jerzy; RANACHOWSKI, Jerzy (Archives of Acoustics, 1984)
The present paper describes a new method of photoacoustic spectroscopy for the investigation of the properties of materials. This method is applied in studies of both inorganic and organic materials, including biological structures.The paper also gives the physical basis of the method, the construction principle of the measuring apparatus and examples of application of photoacoustic spectroscopy in biology and medicine.